CULTURAL TRAUMA AND CONTEMPORARY WOMEN’S WRITING. THE CASE OF SAȘA ZARE’S SOMATIC SCRIPTOTHERAPY - COTOI, Amalia (Studia Universitatis Babeș-Bolyai Philologia, 2025)
Cultural Trauma and Contemporary Women’s Writing. The Case of Sașa Zare’s Somatic Scriptotherapy. Situated at the crossroads of Literary Studies, Trauma Studies, and Memory Studies, this paper examines the conceptualization of “cultural trauma” within trauma theory and its representation in Sașa Zare’s contemporary writing (Dezrădăcinare [Uprooting]) (2022), while also addressing the emergence of a new genre informed by these concerns. The aim of this study is threefold. First, I analyze the contested concept of cultural trauma and its relationship to both clinical studies and women’s writing. Second, I extend Suzette A. Henke’s notion of “scriptotherapy” into somatic scriptotherapy and investigate the emergence of a new genre within contemporary women’s literature. Third, I explore the cultural and traumatic representations of motherhood, alongside the somatic dynamics of the mother–daughter relationship in Dezrădăcinare by Sașa Zare. The principal conclusions of this paper may be summarized as follows. First, Dezrădăcinare demonstrates that the expansion of writing into the exploration of traumatic stressors and processes of individual transformation requires a broader conceptualization of trauma, such as that advanced by theories of cultural trauma. Second, it reveals that the interrelation of procedural memory, therapeutic reenactment, and traumatic outcomes in contemporary women’s writing necessitates the articulation of a new genre. Finally, it shows how different forms of clinical trauma, such as enmeshment, attachment, and developmental trauma, are inextricably bound to the embodiment of motherhood and to the bodily entanglement of the mother–daughter relation. REZUMAT. Trauma culturală și literatura contemporană feminină. Analiza critică a scriiturii somatice în opera Sașei Zare. Situat la intersecția dintre studiile literare, studiile despre traumă (Trauma Studies) și studiile despre memorie (Memory Studies), acest articol examinează conceptualizarea „traumei culturale” în cadrul Trauma Studies și reprezentarea sa în Dezărădăcinare (2022) de Sașa Zare, abordând totodată emergența unui nou gen literar modelat de aceste preocupări. Demersul de față are trei obiective majore. În primul rând, analizez conceptul controversat de traumă culturală și relația sa atât cu studiile clinice, cât și cu scrierile feminine. În al doilea rând, extind noțiunea de „scriptotherapy” propusă de Suzette A. Henke în somatic scriptotherapy și investighez apariția unui nou gen în literatura feminină contemporană. În al treilea rând, explorez reprezentările culturale și traumatice ale maternității, alături de dinamica somatică a relației mamă–fiică în Dezrădăcinare (2022) de Sașa Zare. Concluziile principale ale acestui studiu pot fi rezumate astfel. În primul rând, Dezrădăcinare demonstrează că extinderea scrisului către explorarea factorilor traumatici și a proceselor de transformare individuală reclamă o conceptualizare mai amplă a traumei, precum cea avansată de teoriile traumei culturale. În al doilea rând, evidențiază că legăturile dintre memoria procedurală, reactualizarea terapeutică și consecințele traumatice în scrierile feminine contemporane necesită articularea unui nou gen. În cele din urmă, ilustrează cum diferite forme de traumă clinică, precum enmeshment, attachment, și developmental trauma, sunt inextricabil legate de maternitatea privită ca embodiment și de interdependența corporală a relației mamă–fiică. Cuvinte-cheie: traumă culturală, scriptoterapie somatică, literatura contemporană scrisă de femei, Dezrădăcinare, literatura est-europeană, memorie procedurală, enmeshment trauma, developmental trauma, attachment trauma. Article history: Received 15 July 2025; Revised 06 September 2025; Accepted 09 September 2025; Available online 24 September 2025; Available print 30 September 2025